Understanding patterns of child material deprivation in five regions of the world: A children's rights perspective. (January 2020) - Shamrova, Daria; Lampe, Joana
Highlights: Experience of certain material deprivation pattern varies significantly across the world. Children from Europe have almost no likelihood of belonging to the Extreme Deprivation class. Children living in MENA are more likely to experience housing and mobile deprivation. Children living in Africa are more likely to experience lack of access to digital resources in addition to deficit of basic necessities. Children living in Eastern Europe are more likely to experience transportation deprivation. Abstract: Current research suggests that poverty affects children at different rates across the world (OECD, 2018; Unicef Innocenti Research Center, 2007 ). Additionally, poverty affects children differently – from deprivation of basic needs (ex. lack of food, clothing) to lack of access to digital technology. Previous studies of child poverty and its impact on children have predominantly approached this topic using income-based measures of poverty. This paper employs a material deprivation approach to study child poverty in different cultural contexts. Therefore, this study answers the following questions: Does child material deprivation have different patterns across world regions? If so, what characteristics do these patterns of material deprivation have? Are these patterns of material deprivation more likely to affect certain world regions? This paper utilizes data from the International Survey of Child Well-Being. The data includes children at the age of 12 from Norway, Germany, England, Spain, Malta, Estonia, Romania, Algeria, Israel, Turkey, Ethiopia, and South Africa. The analyses were based on the items available in the Child Material Resource Index. Latent class analysis and multinomial logistic regression were utilized to explore patterns of material deprivation. Findings suggest five patterns of child material deprivation, ranging from extreme to no deprivation. The distribution of these patterns varies significantly across world regions. This study suggests that the distribution of resources to eliminate poverty should be based not only on income-based indicators but should also include an assessment based on perceived deprivation scales, especially in international contexts.